Real driving emissions tests of a light truck operating using a Euro-IV compliant CI engine - Ang, Chuen Yuen (2022)
After the outbreak of ‘Volkswagen Dieselgate’ scandal, the intention to measure real-world driving emission has increased. Research worldwide have outlined that laboratory testing does not reflect the actual vehicle emissions under on-road operating conditions. The aim of this study is to conduct real-driving emission (RDE) testing using a Euro 4-compliant diesel truck on pre-designed test routes under the Malaysian context. CO, CO2, HC, and particulate matter (PM2.5) are the targeted emission pollutants in current study. For trip execution and trip design, the In-Service Conformity (ISC) procedure is applied as a guideline to ensure the significance of data obtained. Vehicle specific power (VSP) approach is applied for emission analysis and the overall results obtained are compared to the regulated emission limit to identify the gaps. The overall brake-based emission factors obtained were 0.178 g/kWh CO, 3.126 g/kWh HC and 0.0002 g/kWh PM2.5. CO and PM2.5 obtained in this study were lower than the regulated emission limit. However, HC emission results obtained were found to be 6 times higher than the regulated EURO IV limit. Findings suggested that emissions results obtained depend strongly on the functional relations and types of emission. CO2 and PM2.5 are more affected by the engine load while CO and HC are affected by the on-road operating conditions. The findings of this study are expected to enhance the knowledge of local automotive industries and assist them in producing better diesel trucks. It is concluded that RDE tests are necessary to ensure the emission are within the regulated limits